Model and control scheme for recirculation mode direct steam generation parabolic trough solar power plants. (15th September 2017) - Guo, Su; Liu, Deyou; Chen, Xingying; Chu, Yinghao; Xu, Chang; Liu, Qunming; Zhou, Ling
Highlights: A nonlinear dynamic model of recirculation DSG parabolic trough is developed. Collector row, water separator and spray attemperator are modeled, respectively. The dynamic behaviors of the collector field are simulated and analyzed. Transfer functions of water level and outlet fluid temperature are derived. Multi-model switching generalized predictive control strategy is developed. Abstract: This work describes and evaluates a new nonlinear dynamic model, and a new generalized predictive control scheme for a collector field of direct steam generation parabolic troughs in recirculation mode. Modeling the dynamic behaviors of collector fields is essential to design, testing and validation of automatic control systems for direct steam generation parabolic troughs. However, the behaviors of two-phase heat transfer fluids impose challenges to simulating and developing process control schemes. In this work, a new nonlinear dynamic model is proposed, based on the nonlinear distributed parameter and the nonlinear lumped parameter methods. The proposed model is used to simulate and analyze the dynamic behaviors of the entire collector field for recirculation mode direct steam generation parabolic troughs under different weather conditions, without excessive computational costs. Based on the proposed model, transfer functions for both the water level of the separator and outlet steam temperatures are derived, and a new multi-model switching generalized predictive control scheme is developed for simulated control of the plant behaviors for a wide region of operational conditions. The proposed control scheme achieves excellent control performance and robustness for systems with long delay, large inertia and time-varying parameters, and efficiently solves the model mismatching problem in direct steam generation parabolic troughs. The performances of the model and control scheme are validated with design data from the project of Integration of Direct steam generation Technology for Electricity Production and experimental data obtained from the DIrect Solar Steam project.